Prevention and control of sewer system overflows MOP FD-17 - McGraw-Hill eBooks; Water Environment Federation. Prevention and Control of Sewer System Overflows Task Force (New York : McGraw-Hill, 2012)
"The purpose of this manual of practice is to provide the information necessary to help managers and engineers understand and analyze an overflow problem (dry weather, CSO [combined sewer overflows], or SSO [sewer system overflows]) and provide guidance in finding the best strategies to reduce or eliminate it. It is also intended to serve as a planning guide in developing long-term control plans for CSOs and SSOs."
Introduction -- Definitions and causes of overflows -- Regulatory overview -- Information management -- System characterization -- System maintenance and management -- Overflow mitigation technologies -- Overflow mitigation plan development and implementation.
Print version c2011.
Includes bibliographical references.
Also issued in print.
Description based on cover image and table of contents, viewed on Dec. 14, 2012.
Keywords: Combined sewer overflows -- Environmental aspects; Water -- Pollution -- Prevention; Sewerage -- Cleaning; Combined sewers; Electronic books